The rest of the story: the microbiome and gastrointestinal infections. (February 2015) - Leslie, Jhansi L; Young, Vincent B
Graphical abstract: Highlights: The gut microbiome is a critical component in many gastrointestinal infections. The microbiota modulates infections through both direct and indirect interactions. Appropriate development of host immunity is dependent on the microbiome. Dissimilar microbial communities may provide similar functions. Abstract : Bacterial infectious diseases are studied primarily as a host–pathogen dyad. However it is increasingly apparent that the gut microbial community is an important participant in these interactions. The gut microbiota influences bacterial infections in a number of ways, including via bacterial metabolism, stimulation of host immunity and direct bacterial antagonism. This review focuses on recent findings highlighting the interplay between the gastrointestinal microbiota, its host and bacterial pathogens; and emphasizes how these interactions ultimately impact our understanding of infectious diseases.